PENERAPAN MODEL COOPERATIVE LEARNING TIPE PICTURE AND PICTURE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRONOLOGIS SISWA DALAM PEMBELAJARAN SEJARAH - Noer Hadi Pratomo; Erlina Wiyanarti; Yeni Kurniawati (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
The background of this research arose from the researcher’s concern to the students’ lack of ability to think chronologically in XI IPS 3 classroom. It is identified by their ignorance to temporal structure concept and low ability in demonstrating the concept of continuity and causality. So the aim of this study focuses in improving the students’ chronological thinking ability through the implementation of cooperative learning model picture and picture type. This cooperative learning model picture and picture type allows students to work together in groups to achieve the learning purpose through pictures as its media. Therefore, by using pictures as media in learning avtivities it is aimed to help students reconstructing historical events. The method used in this study is a classroom action research (CAR), the research design is adapted from the work of Kemmis and Mc. Taggart where it consists of several cycle and each includes several phases; planning (plan), implementation (act), observations (Observe) and reflection (Reflect). The data was collected from observation, interviews, and documentation. Based on the results carried out during the four cycles, it can be concluded that there is a significant increase in the students’ ability to think chronologically. The increase was identified while the implementation of cooperative learning model picture and picture type, the students showed high motivation towards the learning materials, enthusiasm to work together in groups to complete the task, the students become accustomed to write down timeline and the increase of ability to reconstruct events in chronological order. It shows that the implementation of cooperative learning model picture and picture type can improve the students’ ability to think chronologically.